A proposal for a systematic approach to moral philosophy - Christopher Caruana (Language, Culture, Politics)
This article gives a methodological overview of three standards against which it is possible to examine the worth of moral theories and to test their true contribution to ethics. These standards or benchmarks are requirements pertaining to metaethics, moral psychology and practical reason. The proposal is that it is only when a theory answers questions raised by these three areas of inquiry together that such a theory can be said to be a substantive theory of morality. While defending the importance of each area I also provide examples on the way to highlight such areas of relevance.